(NmAGNITNAQ GIDRODINAMIKA (B/s - (NkAULING(B, (Nt(B.s; (NpETROW(B, (Nw(B.(Ng(B.s ((NmOSKWA (B:s (NaTOMIZDAT(B,s, 1978)
(NsPISOK LIT(B. 97 (NNAIMEN(B.s
T.G. Cowling
Keywords: (NdINAMIKA PLAZMYs; (NmAGNITNAQ GAZODINAMIKAs